METHODS OF TEACHING A FOREIGN LANGUAGE IN THE 21ST CENTURY - Nazarova Ziyoda, Nazarova Ziyoda (Журнал иностранных языков и лингвистики, 2021)
As the world is now various and globalized, the probability to talk and collaborate with speakers of distinct language and cultural backgrounds has increased. The foreign language training has also positioned elevated emphasis on learning languages through social activities. In my article, I will provide new guidelines into a curriculum, that tell you what learning methods work best for language teaching, and the role of technological century.